Plan de negocios para la empresa piscicultora-gallinas ponedoras productora y comercializadora “El Galpón del Pez” (2024)
This project aims to evaluate the viability of establishing an integrated fish farm with byproducts derived from the breeding of various domestic species in the department of Meta. The initiative will begin with the construction of a shed for 3,600 Babcock Brown laying hens, which will produce high-quality and semi-Creole eggs, fed with concentrate and natural products to offer a healthy and nutritious product. The feasibility study considers demographic factors, abundant water resources, and the diversity of wildlife and vegetation in the department of Meta. Although local farmers have dedicated themselves to crops such as cocoa, cassava, banana and corn, the uncertainty in the remuneration of these crops and the competition with livestock and rubber cultivation have generated the need to explore new economic alternatives.